Sepakbola sebagai Alat Komunikasi Publik: Studi tentang Peran Tim Nasional dalam Pembentukan Identitas Nasional - Kiki Esa Perdana (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2025)
Football as the most popular sport in Indonesia makes many people think that football is part of themselves. The national team as a representation of the country is often considered a reflection of national identity, so the good or bad achievements of the national team in the international arena are often a measure of how much pride the community has in this most popular sport in Indonesia. This study intends to explain that the role of the national team has a significant impact on the national identity factor, especially for its supporters. By using an understanding of public communication, the role of the national team can be seen in general in forming a national identity, either directly or indirectly. This study uses a qualitative descriptive research method, which can be described as a series of research activities that aim to obtain data results that are purely as they are without any particular conditions, which then emphasizes the meaning rather than numbers, using observation data collection techniques, documents, and literature studies. The results of this study indicate that the national team emerged as an identity arena for many Indonesian people when used as a medium for forming a national identity.